Relevance of rapid, reliable and low-cost diagnostics in the current COVID-19 pandemic - Relevance of rapid; reliable; low-cost diagnostics in the current (Global Journal of Clinical Virology - Peertechz Publications, 2020)
COVID-19 virus has emerged as a global pandemic. This zoonotic virus has known to be originated in China, which within few weeks has spread across the world. The virus has infected millions of people and lakhs have died due to this virus. It has high transmissibility with a reproductive number (Ro) of 2.2. Many cases are reported asymptomatic, hence making the control of the infection a herculean task. Many countries have resorted to lockdowns to flatten the curve of infection, leading to shutting of many businesses and pushing the global economy into severe recession. India's GDP is said to be in negative territory, as expected by Reserve Bank of India. The review summarizes about the global efforts that are been made to develop novel, rapid, reliable and affordable molecular diagnostic assays such as nucleotide and antigen-based detection assays and serological assays. Many of them are under developing stage and few have received an Emergency Use Authorisation (EUA) or Conformite Europeene (CE) certification for their application in different hospitals and clinical settings. For confirmatory diagnosis, such category of molecular diagnostics needs to replace the presently employed Real-Time PCR assays that are high in installation, testing cost and expertise intensive normally resulting in delay for obtaining results. These limitations do not permit an exhaustive testing needed under the current pandemic situation. The new category of rapid, reliable, low cost diagnostic once deployed would effectively help in arresting the community transmission of the disease to a larger extent, thereby easing of lockdown situations and contributes towards revival of economy.